Sistem Pengawasan dan Perlindungan Hukum dalam Tata Kelola Administrasi Negara - Lingga Abi Rahman; Jeora Nitysa Aprily; Muhammad Faishal Fadhlurrahman; Nurul Nurul; Rani Komalasari; Muhammad Luthfi Setiarno Putera (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
This article explores the mechanisms of supervision and legal protection within state administration. Ensuring legal protection for citizens is a vital aspect of governance in democratic nations. Laws serve as tools to regulate rights, obligations, and legal entities, enabling them to fulfill their duties and receive fair treatment. Additionally, the law functions as a protective framework for legal subjects. The legal relationship between the state and its citizens can be governed either by state administrative law or civil law, depending on the state's role and position in upholding the law. The government may act as a civil legal entity or a public official, subjecting its legal actions to either the Civil Code or state administrative law. Mechanisms for supervision and legal protection in state administration include embedded supervision, functional supervision, and external supervision. Furthermore, citizens are afforded legal protection through administrative law mechanisms such as administrative law provisions, administrative appeals, and administrative courts.